Planning and Development af a Creative Business Area Based on Freshwater Fish Cultivation in Pandeglang Regency - Roy Tumpal Pakpahan (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2025)
This study aims to examine the planning and development of a creative business district based on freshwater fish farming in Pandeglang Regency, Banten Province. Pandeglang Regency has significant potential in freshwater aquaculture such as tilapia, carp, catfish, and gourami which is spread across almost all sub-districts. However, this potential has yet to be fully optimized as a driving force for the local economy. Using a qualitative approach that includes observations, in-depth interviews, and document analysis, this research explores the current conditions, strategic planning for creative business areas, and collaboration among government, business actors, academics, and local communities. The findings reveal that despite promising potential, several challenges remain, such as limited product innovation, inadequate supporting infrastructure, and low adoption of digital technology and modern marketing strategies. Therefore, an integrated development strategy is required encompassing the strengthening of production and processing centers, development of educational tourism based on freshwater fish, capacity building through training, and enhanced multi-stakeholder collaboration to create a competitive and sustainable creative business ecosystem. This study is expected to serve as both policy recommendations for local government and an academic reference for the development of similar sectors in other regions with comparable potential.